Maryam bint 'Imran as "Our Lady of Muslims" - Longhurst, Christopher Evan (Journal of ecumenical studies, 2017)
The article refers to Mary, the mother of Jesus, and discusses how appropriate it may be to refer to her as Our Lady and Our Lady of Muslims. Topics discussed include the interreligious dialogue between Muslims and Christians, commonalities between Islam and Anglo-Roman Catholicism, and the significance of Mary, or Maryam bint Imran for Muslims.